Research of Locati Rapid Test Method for Gear Contact Fatigue Limit - Wu Ping’an; Wang Tie; Zhang Ruiliang; Wu Zhifei; Liu Yaqiong; Zhang Rui (Jixie chuandong)
The fatigue limit of the material plays a vital role,when the gear life and reliability design. Because the Locati rapid test method need less time and data,and the test result is more reliable,which becomes the common method of gear fatigue test. But this method must refer to the related test data to determine the reference curve. A more reliable data processing method is discussed,compared with the traditional method,neither need to determine the reference curve in advance,nor need to calculate the sum of fatigue damage accumulation,but directly solve the fatigue curve equation to obtain the relevant fatigue limit. The improved method is simply solves the equation,the calculation process is simple and the result is more credible and accurate. The fatigue test can verify that this method is feasible,which provides a theoretical basis for using Locati rapid test method to obtain the fatigue limit of the related material.